Influence of nitrogen levels and weed management practices on productivity of rice under aerobic conditions - Prakash, Chandra; Koli, N. R.; Shivran, R. K.; Sharma, J. C. (Annals of Agricultural Research, 2014)
A field experiment was conducted to study the effect of nitrogen levels and weed control methods on growth, yield attributes and yield of rice. The results revealed that the rice variety 'IR-64' recorded maximum grain (3.46 t ha-1), straw (4.84 t ha-1) and biological yield (8.30 t ha-1) with the application of 125 kg N ha-1 under aerobic conditions which was statistically at par with application of 100 kg N ha-1. On the other hand, different weed control practices also gave significantly higher grain yield of aerobic rice. The application of pendimethalin @ 1.0 kg a.i. ha-1at 2 DAS + rice : dhaincha (1:1) + 2,4- D Na salt @ 0.8 kg a.i. ha-1 at 25 DAS recorded excellent performance and contributed grain, straw and biological yield of 3.98, 5.55 & 9.53 t ha-1, respectively. Weed dry weight was recorded at 55 DAS shows that application of pendimethalin @ 1.0 kg a.i. ha-1at 2 DAS + rice : dhaincha (1:1) + 2,4-D Na salt @ 0.8 kg a.i. ha-1 at 25 DAS recorded significantly lowest weed biomass as compared to other weed control treatments.